COVID-19 and pregnancy: main clinical and laboratory manifestations, and their possible complications, an integrative literature review (Research, Society and Development, 2022)
After the institution of the pandemic, pregnant women were placed in the risk group and advised to take additional precautions to avoid complications and infections. It is important to address the quality of life and care for pregnant women within this context, especially due to the new demands, the need to develop follow-up and support strategies. Thus, the research aimed to synthesize the evidence available in the scientific literature aimed at pregnant women affected by COVID-19, as well as to gather the main information about symptoms, complications and severity. This is an integrative literature review, carried out through the electronic databases Scientific Electronic Library Online (Scielo), Academic Journals and Google Scholar. Twenty articles were selected according to inclusion and exclusion criteria. The results found presented as main symptoms: cough, headache, muscle pain, fever, odynophagia, dyspnea and anosmia. However, the symptoms of the infection can overlap with the physiological changes of pregnancy. In more severe cases, there is a risk of developing preeclampsia and/or hypertensive changes, gestational diabetes and low birth weight. Symptoms of pregnant women vary as well as the general population. The chances of complications are also similar and require greater concern if they are associated with previous or acquired comorbidities during pregnancy. As they are considered a risk group, pregnant women should always be aware of any signs and symptoms, in addition to reinforcing preventive measures.